Induction of RAC1 protein translation and MKK7/JNK-dependent autophagy through dicer/miR-145/SOX2/miR-365a axis contributes to isorhapontigenin (ISO) inhibition of human bladder cancer invasion - Xiaohui Hua; Daimin Xiang; Mengxin Guo; Xiaohui Qian; Ruifan Chen; Tengda Li; Zhongxian Tian; Jiheng Xu; Chao Huang; Qipeng Xie; Chuanshu Huang (Cell Death and Disease, 2022)
Abstract Although our previous studies have identified that isorhapontigenin (ISO) is able to initiate autophagy in human bladder cancer (BC) cells by activating JNK/C-Jun/SESN2 axis and possesses an inhibitory effect on BC cell growth, association of autophagy directly with inhibition of BC invasion has never been explored. Also, upstream cascade responsible for ISO activating JNK remains unknown. Thus, we explored both important questions in the current study and discovered that ISO treatment initiated RAC1 protein translation, and its downstream kinase MKK7/JNK phosphorylation/activation, and in turn promoted autophagic responses in human BC cells. Inhibition of autophagy abolished ISO inhibition of BC invasion, revealing that autophagy inhibition was crucial for ISO inhibition of BC invasion. Consistently, knockout of RAC1 also attenuated induction of autophagy and inhibition of BC invasion by ISO treatment. Mechanistic studies showed that upregulation of RAC1 translation was due to ISO inhibition of miR-365a transcription, which reduced miR-365a binding to the 3’-UTR of RAC1 mRNA. Further study indicated that inhibition of miR-365a transcription was caused by downregulation of its transcription factor SOX2, while ISO-promoted Dicer protein translation increased miR-145 maturation, and consequently downregulating SOX2 expression. These findings not only provide a novel insight into the understanding association of autophagy induction with BC invasion inhibition by ISO, but also identify an upstream regulatory cascade, Dicer/miR145/SOX2/miR365a/RAC1, leading to MKK7/JNKs activation and autophagy induction.